Murine Pancreatic Beta TC3 Cells Show Greater 2′, 5′-Oligoadenylate Synthetase (2′5′AS) Antiviral Enzyme Activity and Apoptosis Following IFN-α or Poly(I:C) Treatment than Pancreatic Alpha TC3 Cells. (5th October 2009) - Li, M.; Zheng, D.-J.; Field, L. L.; Bonnevie-Nielsen, V.
Abstract : Type 1 diabetes is caused by autoimmune destruction of pancreatic beta cells, possibly virus initiated. Virus infection induces alpha-interferon (IFN-α ), leading to upregulation of genes encoding double-stranded (ds) RNA-dependent antiviral enzymes2 ′, 5 ′ -oligoadenylate synthetase (2 ′ 5 ′ AS) and PKR (p68). To investigate whether beta cell specificity could be due to antiviral differences between beta and alpha cells, we treated beta and alpha TC3 cell lines with IFN-α and/or poly(I:C) (a synthetic dsRNA). Results showed that, following IFN-α stimulation, increases in2 ′ 5 ′ AS levels and activities were significantly higher in beta than alpha cells( P < .001 ), whereas increases in PKR level and activity were comparable in the two cell types. Poly(I:C) stimulated2 ′ 5 ′ AS activity in beta but not alpha cells, and co-transfection IFN-α plus poly(I:C) induced apoptosis in beta but not alpha cells. These findings suggest that the elevated2 ′ 5 ′ AS response of pancreatic beta cells could render them particularly vulnerable to damage and/or apoptosis during virus infection.